In vitro bioactivity and degradability of β‐tricalcium phosphate porous scaffold fabricated via selective laser sintering. (18th April 2013) - Shuai, Cijun; Zhuang, Jingyu; Hu, Huanlong; Peng, Shuping; Liu, Defu; Liu, Jinglin
Abstract Porous scaffolds consisting of β‐tricalcium phosphate (β‐TCP) were successfully fabricated via selective laser sintering. The scaffolds had a controlled microstructure and totally interconnected porous structure. The microstructure and mechanical properties were studied. The bioactivity and degradability of scaffolds were evaluated through the simulated body fluid (SBF) cultivation experiment. The formation of a biologically active carbonate apatite layer on the surface after immersion in SBF was demonstrated using scanning electron microscope, energy dispersive X‐ray, and Fourier transform infrared spectroscopy. Fast nucleation and growth of the carbonate apatite crystals were observed to occur all through the specimen surfaces. The phenomenon was explained in terms of the distribution and dispersion of inorganic phases in the scaffolds and the ionic activity products of the apatite in the SBF. The calculation results of weight loss and Ca/P molar ratio also suggest the good bioactivity and degradability of the scaffolds. These indicate that the β‐TCP porous ceramic scaffold is a potential candidate scaffold for bone tissue engineering.